Assessing the Potential of Farmer Field Schools (FFS) to Fight Poverty and Foster Innovation in East Africa - Davis, Kristin E. (International Food Policy Research Institute, 2012)
This is a unique primary household and community level survey data in Kenya, Tanzania, and Uganda. The study was started in 2008/2009 and the data collection took place in selected districts in Kenya, Tanzania, and Uganda. The project’s goal was to provide strong evidence to policy makers and other stakeholders in development on the effectiveness of Farmer Field Schools (FFS) in fighting poverty and fostering innovation. The specific objectives of the field data collection were to characterize farm households in terms of poverty and well-being, members-and non- FFS members, on the basis of socio-economic parameters; analyze farmers’ access to agricultural services (markets, credit and extension); and assess household’s level of individual and collective empowerment. (2012-04-09)